Heat insulation type fireproof glass and manufacturing method thereof
By combining polydopamine-modified tetra-acid zinc oxide whiskers with octa-amino POSS modified polyacrylamide gel layer, a stable whisker skeleton structure is solved, and the existing composite fire-resistant glass thermal insulation performance and UV radiation resistance are solved. The problem of insufficient performance achieves efficient fire resistance, heat insulation and aging resistance.
Patent Information
- Application Number
- CN202411652910.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The existing composite fireproof glass has limited thermal insulation performance, poor UV radiation resistance, and poor aging resistance of polyacrylamide gel materials.
Polydopamine-modified tetra-acid zinc oxide whiskers are combined with octa-amino POSS modified polyacrylamide gel layer to form a stable whisker framework structure, and the thermal insulation fire-resistant glass is improved by composite flame retardant and crosslinking agent. Fireproof, heat insulation and aging resistance.
It significantly improves the fire resistance, thermal insulation and aging resistance of heat-insulating fire-resistant glass, can maintain structural stability in high temperature environments and effectively resist ultraviolet radiation.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to a heat-insulating fireproof glass and a manufacturing method thereof. Background Art
[0002] Fire prevention is an important part of building safety design. With the implementation of relevant fire prevention regulations in various countries and the development of the construction industry, various types of fireproof materials for buildings have received more and more attention. Fireproof glass has fireproof and heat-insulating properties that ordinary glass does not have, as well as transparent and beautiful material properties. It maximizes the harmony and unity of building fire prevention and architectural aesthetics, and is widely used in fireproof partitions, fire partitions, fireproof doors and windows and other building parts of large public buildings. At present, the market demand for fireproof glass in countries around the world is increasing year by year.
[0003] Fireproof glass includes composite fireproof glass. The heat insulation and heat radiation protection functions of composite fireproof glass can make the glass structure maintain structural integrity and heat insulation within a specified time when a fire occurs, so that people escaping from the glass back from the fire are protected from high temperature heat radiation, and at the same time prevent combustible materials in other areas from being ignited by high temperature and heat radiation within a certain period of time. At present, the composite fireproof glass on the market is mainly infused fireproof glass.
[0004] The fireproof adhesive material of composite fireproof glass is mainly made of acrylamide, methylenebisacrylamide and other ingredients. The fireproof adhesive liquid is poured into the glass cavity sealed by flame-retardant adhesive strips on all sides by grouting method. The organic network structure formed by cross-linking and curing of acrylamide and methylenebisacrylamide serves as the matrix, and additives such as flame retardants are fixed in the above organic network. However, at present, the effect of pure polyacrylamide gel on improving the thermal insulation performance of composite fireproof glass is limited, and the anti-ultraviolet radiation performance of composite fireproof glass is very poor. Even if it is used indoors, the aging resistance of polyacrylamide gel material at room temperature is not optimistic. Summary of the invention
[0005] The object of the present invention is to provide a heat-insulating fireproof glass and a manufacturing method thereof, wherein the heat-insulating fireproof glass has excellent fireproof performance, heat-insulating performance and aging resistance.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A heat-insulating fireproof glass comprises a fire-facing glass layer and a back-facing glass layer, wherein a polyacrylamide gel layer is filled between the fire-facing glass layer and the back-facing glass layer, and the polyacrylamide gel layer comprises the following raw materials: acrylamide, octaamino POSS, polydopamine-modified tetra-needle zinc oxide whisker, composite flame retardant, crosslinking agent, tetramethylethylenediamine, initiator, and deionized water; The mass ratio of the acrylamide, octaamino POSS and polydopamine modified tetrapod-shaped zinc oxide whisker is 30-38:2.5-4:1.5-2.2.
[0007] Preferably, the polyacrylamide gel layer comprises the following raw materials in parts by weight: 30-38 parts of acrylamide, 2.5-4 parts of octaamino POSS, 1.5-2.2 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 3.5-7 parts of composite flame retardant, 0.35-0.6 parts of crosslinking agent, 0.12-0.15 parts of tetramethylethylenediamine, 0.15-0.2 parts of initiator, and 170-200 parts of deionized water.
[0008] Preferably, the method for preparing the polydopamine-modified tetrapod-shaped zinc oxide whiskers comprises the following steps: Dopamine hydrochloride is added to a Tris-HCl buffer solution with a pH value of 8.5-9, and the mixture is stirred and mixed. Then, tetrapod-shaped zinc oxide whiskers are added, stirred for reaction, and then centrifuged, washed, and dried to prepare polydopamine-modified tetrapod-shaped zinc oxide whiskers.
[0009] Preferably, the mass volume ratio of the tetrapod-shaped zinc oxide whisker, dopamine hydrochloride, and Tris-HCl buffer solution is 1 g: 0.5-1 g: 500-1000 ml; and the concentration of the Tris-HCl buffer solution is 0.03-0.06 mol / L.
[0010] Preferably, the diameter of the four-needle zinc oxide whisker is 1-3 μm.
[0011] Preferably, the stirring reaction temperature is 40-45° C., and the stirring reaction time is 6-9 h.
[0012] Preferably, the composite flame retardant is composed of diammonium phosphate and urea in a mass ratio of 3-8:5-10.
[0013] Preferably, the fire-facing glass layer and the back-fire glass layer are both tempered glass with a thickness of 4-6 mm; and the thickness of the polyacrylamide gel layer is 5-7 mm.
[0014] Preferably, the cross-linking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate.
[0015] As a general inventive concept, the present invention also provides a method for manufacturing heat-insulating fire-resistant glass, comprising the following steps: S1: splicing and bonding the fire-facing glass layer and the back-facing glass layer with flame-retardant sealant to form a hollow glass component; S2: Take 10 / 1-12 / 1 deionized water, add initiator and tetramethylethylenediamine, stir to prepare initiator / tetramethylethylenediamine solution; add acrylamide, octaamino POSS, polydopamine modified tetra-needle zinc oxide whisker, crosslinking agent, composite flame retardant to the remaining amount of deionized water, stir and ultrasonically disperse for 7-12h to obtain a mixed liquid; then drip the initiator / tetramethylethylenediamine solution while stirring; after the dripping is completed, stir to obtain a perfusion liquid; S3: pouring the pouring liquid into the cavity of the hollow glass component, and after it is filled, sealing it with a sealant to obtain a component to be cured; S4: placing the workpiece to be cured in an oven for curing treatment to prepare a heat-insulating fire-resistant glass.
[0016] The beneficial effects of the present invention are: 1. The tetrapod-modified zinc oxide whiskers of the present invention are firmly combined with the polyacrylamide gel material. Combined with the unique tetrapod-shaped structure of the tetrapod-shaped zinc oxide whiskers, a stable whisker skeleton structure can be formed in the polyacrylamide gel layer, which can well exert the fireproof and heat-insulating properties of the tetrapod-shaped zinc oxide whiskers and improve the aging resistance of the polyacrylamide gel layer.
[0017] 2, the present invention adopts eight amino POSS modified polyacrylamides, the polyacrylamide gel material obtained has more stable spatial network structure, and the bonding strength between the polyacrylamide gel layer and the glass layer is also stronger, thereby can effectively improve the structural stability of the polyacrylamide gel layer under hot environment, thereby is conducive to strengthening heat insulation and fireproof performance. In addition, adopt eight amino POSS modified polyacrylamides also can effectively strengthen the anti-aging performance of the polyacrylamide gel layer.
[0018] 3. The present invention modifies polyacrylamide by using octaamino POSS and polydopamine-modified tetrapod-shaped zinc oxide whiskers, so that the obtained heat-insulating fireproof glass has excellent fireproof performance, heat-insulating performance and aging resistance. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Embodiment 1: A heat-insulating fireproof glass comprises a fire-facing glass layer and a back-to-fire glass layer, both of which are tempered glass with a thickness of 5 mm, and a polyacrylamide gel layer is filled between the fire-facing glass layer and the back-to-fire glass layer, and the thickness of the polyacrylamide gel layer is 5 mm.
[0021] The polyacrylamide gel layer includes the following raw materials in parts by weight: 33 parts of acrylamide, 4 parts of octaamino POSS, 2 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 6 parts of composite flame retardant, 0.5 parts of N,N-methylenebisacrylamide, 0.12 parts of tetramethylethylenediamine, 0.18 parts of ammonium persulfate, and 200 parts of deionized water.
[0022] The method for preparing the polydopamine-modified tetrapod-shaped zinc oxide whisker comprises the following steps: Dopamine hydrochloride was added to a Tris-HCl buffer solution with a pH value of 9 and a concentration of 0.03 mol / L, and after stirring and mixing, tetrapod-shaped zinc oxide whiskers with a diameter of 1-3 μm were added, and the mixture was stirred and reacted at 45° C. for 9 h, and then centrifuged, washed, and dried to obtain polydopamine-modified tetrapod-shaped zinc oxide whiskers.
[0023] The mass volume ratio of the tetrapod-shaped zinc oxide whisker, dopamine hydrochloride, and Tris-HCl buffer solution is 1 g: 1 g: 1000 ml.
[0024] The composite flame retardant is composed of diammonium phosphate and urea in a mass ratio of 8:5.
[0025] The method for manufacturing the above-mentioned heat-insulating fireproof glass comprises the following steps: S1: splicing and bonding the fire-facing glass layer and the back-facing glass layer with flame-retardant sealant to form a hollow glass component; S2: Take 12 / 1 deionized water, add ammonium persulfate and tetramethylethylenediamine, stir to prepare initiator / tetramethylethylenediamine solution; add acrylamide, octaamino POSS, polydopamine-modified tetra-needle zinc oxide whisker, N,N-methylenebisacrylamide, and composite flame retardant to the remaining amount of deionized water, stir and ultrasonically disperse for 7 hours to obtain a mixed liquid; then drip the ammonium persulfate / tetramethylethylenediamine solution while stirring; after the dripping is completed, stir to obtain a perfusion liquid; S3: pouring the pouring liquid into the cavity of the hollow glass component, and after it is filled, sealing it with a sealant to obtain a component to be cured; S4: placing the workpiece to be cured in an oven for curing treatment to prepare a heat-insulating fire-resistant glass.
[0026] Embodiment 2: A heat-insulating fireproof glass comprises a fire-facing glass layer and a back-to-fire glass layer, both of which are tempered glass with a thickness of 4 mm, and a polyacrylamide gel layer is filled between the fire-facing glass layer and the back-to-fire glass layer, and the thickness of the polyacrylamide gel layer is 6 mm.
[0027] The polyacrylamide gel layer includes the following raw materials in parts by weight: 38 parts of acrylamide, 3.5 parts of octaamino POSS, 1.5 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 7 parts of composite flame retardant, 0.35 parts of N,N-methylenebisacrylamide, 0.13 parts of tetramethylethylenediamine, 0.15 parts of ammonium persulfate, and 170 parts of deionized water.
[0028] The method for preparing the polydopamine-modified tetrapod-shaped zinc oxide whisker comprises the following steps: Dopamine hydrochloride was added to a Tris-HCl buffer solution with a pH value of 8.5 and a concentration of 0.05 mol / L, and after stirring and mixing, tetrapod-shaped zinc oxide whiskers with a diameter of 1-3 μm were added, and the mixture was stirred and reacted at 40° C. for 6 h, and then centrifuged, washed, and dried to obtain polydopamine-modified tetrapod-shaped zinc oxide whiskers.
[0029] The mass volume ratio of the tetrapod-shaped zinc oxide whisker, dopamine hydrochloride, and Tris-HCl buffer solution is 1 g:0.5 g:500 ml.
[0030] The composite flame retardant is composed of diammonium phosphate and urea in a mass ratio of 3:8.
[0031] The method for manufacturing the above-mentioned heat-insulating fireproof glass comprises the following steps: S1: splicing and bonding the fire-facing glass layer and the back-facing glass layer with flame-retardant sealant to form a hollow glass component; S2: Take 10 / 1 deionized water, add ammonium persulfate and tetramethylethylenediamine, stir to prepare initiator / tetramethylethylenediamine solution; add acrylamide, octaamino POSS, polydopamine-modified tetra-needle zinc oxide whisker, N,N-methylenebisacrylamide, and composite flame retardant to the remaining amount of deionized water, stir and ultrasonically disperse for 12 hours to obtain a mixed liquid; then drip the ammonium persulfate / tetramethylethylenediamine solution while stirring; after the dripping is completed, stir to obtain a perfusion liquid; S3: pouring the pouring liquid into the cavity of the hollow glass component, and after it is filled, sealing it with a sealant to obtain a component to be cured; S4: placing the workpiece to be cured in an oven for curing treatment to prepare a heat-insulating fire-resistant glass.
[0032] Embodiment 3: A heat-insulating fireproof glass comprises a fire-facing glass layer and a back-to-fire glass layer, both of which are tempered glass with a thickness of 6 mm, and a polyacrylamide gel layer is filled between the fire-facing glass layer and the back-to-fire glass layer, and the thickness of the polyacrylamide gel layer is 7 mm.
[0033] The polyacrylamide gel layer includes the following raw materials in parts by weight: 30 parts of acrylamide, 2.5 parts of octaamino POSS, 2.2 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 3.5 parts of composite flame retardant, 0.6 parts of N,N-methylenebisacrylamide, 0.15 parts of tetramethylethylenediamine, 0.2 parts of ammonium persulfate, and 180 parts of deionized water.
[0034] The method for preparing the polydopamine-modified tetrapod-shaped zinc oxide whisker comprises the following steps: Dopamine hydrochloride was added to a Tris-HCl buffer solution with a pH value of 9 and a concentration of 0.06 mol / L, and after stirring and mixing, tetrapod-shaped zinc oxide whiskers with a diameter of 1-3 μm were added, and the mixture was stirred and reacted at 42° C. for 7 h, and then centrifuged, washed, and dried to obtain polydopamine-modified tetrapod-shaped zinc oxide whiskers.
[0035] The mass volume ratio of the tetrapod-shaped zinc oxide whisker, dopamine hydrochloride, and Tris-HCl buffer solution is 1 g:0.8 g:800 ml.
[0036] The composite flame retardant is composed of diammonium phosphate and urea in a mass ratio of 5:10.
[0037] The method for making the above-mentioned heat-insulating fireproof glass is the same as that in Example 1.
[0038] Embodiment 4: A heat-insulating fireproof glass comprises a fire-facing glass layer and a back-to-fire glass layer, both of which are tempered glass with a thickness of 5 mm, and a polyacrylamide gel layer is filled between the fire-facing glass layer and the back-to-fire glass layer, and the thickness of the polyacrylamide gel layer is 6 mm.
[0039] The polyacrylamide gel layer includes the following raw materials in parts by weight: 35 parts of acrylamide, 2.5 parts of octaamino POSS, 2 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 4.5 parts of composite flame retardant, 0.35 parts of N,N-methylenebisacrylamide, 0.12 parts of tetramethylethylenediamine, 0.18 parts of ammonium persulfate, and 200 parts of deionized water.
[0040] The preparation method of the polydopamine modified tetrapod-shaped zinc oxide whisker is the same as that of Example 1. The composite flame retardant is the same as that of Example 1.
[0041] The method for making the above-mentioned heat-insulating fireproof glass is the same as that in Example 1.
[0042] Embodiment 5: A heat-insulating fireproof glass comprises a fire-facing glass layer and a back-to-fire glass layer, both of which are tempered glass with a thickness of 6 mm, and a polyacrylamide gel layer is filled between the fire-facing glass layer and the back-to-fire glass layer, and the thickness of the polyacrylamide gel layer is 7 mm.
[0043] The polyacrylamide gel layer comprises the following raw materials in parts by weight: 30 parts of acrylamide, 3.5 parts of octaamino POSS, 2.2 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 6 parts of composite flame retardant, 0.55 parts of N,N-methylenebisacrylamide, 0.15 parts of tetramethylethylenediamine, 0.15 parts of ammonium persulfate, and 180 parts of deionized water.
[0044] The preparation method of the polydopamine modified tetrapod-shaped zinc oxide whisker is the same as that of Example 3. The composite flame retardant is the same as that of Example 2.
[0045] The method for making the above-mentioned heat-insulating fireproof glass is the same as that in Example 2.
[0046] Embodiment 6: A heat-insulating fireproof glass comprises a fire-facing glass layer and a back-to-fire glass layer, both of which are tempered glass with a thickness of 5 mm, and a polyacrylamide gel layer is filled between the fire-facing glass layer and the back-to-fire glass layer, and the thickness of the polyacrylamide gel layer is 5 mm.
[0047] The polyacrylamide gel layer comprises the following raw materials in parts by weight: 35 parts of acrylamide, 3 parts of octaamino POSS, 2 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 4 parts of composite flame retardant, 0.5 parts of N,N-methylenebisacrylamide, 0.15 parts of tetramethylethylenediamine, 0.2 parts of ammonium persulfate, and 170 parts of deionized water.
[0048] The preparation method of the polydopamine modified tetrapod-shaped zinc oxide whisker is the same as that of Example 2. The composite flame retardant is the same as that of Example 3.
[0049] The method for making the above-mentioned heat-insulating fireproof glass is the same as that in Example 2.
[0050] Comparative Example 1: Different from Example 6, the raw material of the polyacrylamide gel layer does not contain octaamino POSS.
[0051] Comparative Example 2: Different from Example 6, the raw material of the polyacrylamide gel layer does not contain polydopamine-modified tetrapod-shaped zinc oxide whiskers.
[0052] Performance Test: According to GB / T12513-2006 “Fire resistance test method for glass-mounted components”, the fire resistance performance test of the heat-insulating fire-resistant glass in the embodiment and the comparative example was carried out, including the fire-resistant heat insulation time and the fire-resistant integrity time.
[0053] The light transmittance of the heat-insulating fire-resistant glass is tested. The light transmittance is the light transmittance of the finished product of the heat-insulating fire-resistant glass at 25°C.
[0054] Aging resistance test: temperature range is 45±5℃; the distance between the sample and the lamp axis is 230㎜; the light source is an ozone-free quartz tube medium-pressure mercury vapor arc lamp, the lamp power is 750W, the lamp voltage is 500±50V, the glass is treated for 100h, and then the transmittance of the thermal insulation fireproof glass is tested.
[0055] The specific test results are shown in Table 1.
[0056] Table 1 Performance test results of heat-insulating fire-resistant glass Fire resistance and heat insulation time / min Fire resistance integrity time / min Transmittance / % Transmittance after aging resistance test / % Example 1 ≥90 ≥90 89.3 88.0 Example 2 ≥90 ≥90 88.9 87.3 Example 3 ≥90 ≥90 89.1 87.4 Example 4 ≥90 ≥90 88.5 86.9 Example 5 ≥90 ≥90 88.7 86.4 Example 6 ≥90 ≥90 89.0 87.5 Comparative Example 1 ≥60 ≥60 88.8 78.2 Comparative Example 2 ≥60 ≥60 89.5 75.5 As shown in Table 1, the fire resistance and heat insulation and fire integrity of the heat-insulating fireproof glass prepared in Example 1 of the present invention can both meet the Class A requirements, and have good aging resistance. By comparing Comparative Examples 1-2 and Example 6, it can be seen that without adding octaamino POSS or polydopamine-modified tetra-needle zinc oxide whiskers to modify the polyacrylamide gel layer, the fire resistance and heat insulation and fire integrity of the heat-insulating fireproof glass only meet the Class B requirements, and the aging resistance is also significantly reduced.
[0057] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A heat-insulating fireproof glass, comprising a fire-facing glass layer and a back-fire glass layer, characterized in that: A polyacrylamide gel layer is filled between the fire-facing glass layer and the back-facing glass layer, and the polyacrylamide gel layer includes the following raw materials: Acrylamide, octaamino POSS, polydopamine-modified tetrapod-shaped zinc oxide whisker, composite flame retardant, crosslinking agent, tetramethylethylenediamine, initiator, deionized water; The mass ratio of the acrylamide, octaamino POSS and polydopamine modified tetrapod-shaped zinc oxide whisker is 30-38:2.5-4:1.5-2.
2.
2. The heat-insulating fireproof glass according to claim 1, characterized in that: The polyacrylamide gel layer comprises the following raw materials in parts by weight: 30-38 parts of acrylamide, 2.5-4 parts of octaamino POSS, 1.5-2.2 parts of polydopamine-modified tetrapod-shaped zinc oxide whiskers, 3.5-7 parts of composite flame retardant, 0.35-0.6 parts of crosslinking agent, 0.12-0.15 parts of tetramethylethylenediamine, 0.15-0.2 parts of initiator and 170-200 parts of deionized water.
3. The heat-insulating fireproof glass according to claim 1, characterized in that: The preparation method of the polydopamine-modified tetrapod-shaped zinc oxide whisker comprises the following steps: Dopamine hydrochloride is added to a Tris-HCl buffer solution with a pH value of 8.5-9, and the mixture is stirred and mixed. Then, tetrapod-shaped zinc oxide whiskers are added, stirred for reaction, and then centrifuged, washed, and dried to prepare polydopamine-modified tetrapod-shaped zinc oxide whiskers.
4. The heat-insulating fireproof glass according to claim 3, characterized in that: The mass volume ratio of the tetrapod-shaped zinc oxide whisker, dopamine hydrochloride and Tris-HCl buffer solution is 1g: 0.5-1g: 500-1000ml; the concentration of the Tris-HCl buffer solution is 0.03-0.06mol / L.
5. The heat-insulating fireproof glass according to claim 3, characterized in that: The diameter of the four-needle zinc oxide whisker is 1-3 μm.
6. The heat-insulating fireproof glass according to claim 3, characterized in that: The stirring reaction temperature is 40-45° C., and the stirring reaction time is 6-9 hours.
7. The heat-insulating fireproof glass according to claim 1, characterized in that: The composite flame retardant is composed of diammonium phosphate and urea in a mass ratio of 3-8:5-10.
8. The heat-insulating fireproof glass according to claim 1, characterized in that: The fire-facing glass layer and the back-fire glass layer are both tempered glass with a thickness of 4-6 mm; the thickness of the polyacrylamide gel layer is 5-7 mm.
9. The heat-insulating fireproof glass according to claim 1, characterized in that: The cross-linking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate.
10. The method for manufacturing heat-insulating fireproof glass according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: splicing and bonding the fire-facing glass layer and the back-facing glass layer with flame-retardant sealant to form a hollow glass component; S2: Take 10 / 1-12 / 1 deionized water, add initiator and tetramethylethylenediamine, stir to prepare initiator / tetramethylethylenediamine solution; add acrylamide, octaamino POSS, polydopamine modified tetra-needle zinc oxide whisker, crosslinking agent, composite flame retardant to the remaining amount of deionized water, stir and ultrasonically disperse for 7-12h to obtain a mixed liquid; then drip the initiator / tetramethylethylenediamine solution while stirring; after the dripping is completed, stir to obtain a perfusion liquid; S3: pouring the pouring liquid into the cavity of the hollow glass component, and after it is filled, sealing it with a sealant to obtain a component to be cured; S4: placing the workpiece to be cured in an oven for curing treatment to prepare a heat-insulating fire-resistant glass.
Citation Information
Cited By
Nano-silicon composite fireproof laminated glass
CN121777520A